Metode Pemicuan dalam Upaya Meningkatkan Budaya Pemberantasan Sarang Nyamuk (PSN) pada Masyarakat - Chandra, Emilia; Zunidra, Zunidra; Ariyadi, Bambang; Ahyanti, Mei (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to produce a triggering method to improve the culture of eradicating mosquito nests (PSN) in the community. The method used is quantitative research with research and development (R&D) design. The research results show that the PSN Mobile Triggering education model, namely the field triggering model followed by Android-based triggering, was declared feasible after the validation stage with 100% health promotion experts, 94.55% IT experts, 92% educational technology experts, and 80 practitioners. % and 93.85% one-on-one trials, 95% small group trials, and 96% large group trials. The PSN Mobile Trigger product effectively increases household mosquitoes' knowledge, attitudes, and behavior by up to 100% in eradicating mosquito nests. In conclusion, the educational model is feasible and effective to use to increase the knowledge, attitudes, and behavior of Jumantik Rumah in destroying mosquito nests. Keywords: Android Based Application; Dengue Hemorrhagic Fever; Trigger Education; Eradication of Mosquito Nests, Mosquito Breeding Sites